Long-Term Accuracy of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Interferon-γ Release Assay and Its Application in Household Investigation. (25th January 2022) - Murugesan, Kanagavel; Jagannathan, Prasanna; Altamirano, Jonathan; Maldonado, Yvonne A; Bonilla, Hector F; Jacobson, Karen B; Parsonnet, Julie; Andrews, Jason R; Shi, Run Zhang; Boyd, Scott; Pinsky, Benjamin A; Singh, Upinder; et al.
Abstract: Background: An immunodiagnostic assay that sensitively detects a cell-mediated immune response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is needed for epidemiological investigation and for clinical assessment of T- cell-mediated immune response to vaccines, particularly in the context of emerging variants that might escape antibody responses. Methods: The performance of a whole blood interferon-gamma (IFN-γ) release assay (IGRA) for the detection of SARS-CoV-2 antigen-specific T cells was evaluated in coronavirus disease 2019 (COVID-19) convalescents tested serially up to 10 months post-infection and in healthy blood donors. SARS-CoV-2 IGRA was applied in contacts of households with index cases. Freshly collected blood in the lithium heparin tube was left unstimulated, stimulated with a SARS-CoV-2 peptide pool, and stimulated with mitogen. Results: The overall sensitivity and specificity of IGRA were 84.5% (153/181; 95% confidence interval [CI]: 79.0–89.0) and 86.6% (123/142; 95% CI: 80.0–91.2), respectively. The sensitivity declined from 100% (16/16; 95% CI: 80.6–100) at 0.5-month post-infection to 79.5% (31/39; 95% CI: 64.4–89.2) at 10 months post-infection ( P < .01). The IFN-γ response remained relatively robust at 10 months post-infection (3.8 vs 1.3 IU/mL, respectively). In 14 households, IGRA showed a positivity rate of 100% (12/12) and 65.2% (15/23), and IgG of 50.0% (6/12) and 43.5% (10/23) in index cases and contacts, respectively, exhibiting a difference of + 50% (95% CI: +25.4 to +74.6) and +21.7% (95% CI: +9.23 to +42.3), respectively. Either IGRA or IgG was positive in 100% (12/12) of index cases and 73.9% (17/23) of contacts. Conclusions: The SARS-CoV-2 IGRA is a useful clinical diagnostic tool for assessing cell-mediated immune response to SARS-CoV-2. Abstract : SARS-CoV-2 immunodiagnostics are needed to identify infected individuals in order to understand the transmission dynamics of emerging variants and to assess vaccine response. Interferon-gamma release assay maintains sensitivity 10 months post-infection in convalescents and detects more household contacts than IgG.